Considerations about the current state of ethics in research in argentine - Outomuro, Delia (Acta Bioethica, 2004)
The purposes of this paper are: 1) to analyze the current state of ethics in research in Argentine from the observations made by our group in national research magazines and from a critic review of the law; 2) to put forward some new strategies focused in making research secure and ethical, and especially 2.a) the independence of REC; 2.b) the need for standards, vouching for, accreditation and auditing REC; 2.c) the need for reviewing CIOMS 1991 norms taking into account not only biological risks but also psychological, social, cultural and legal ones; 2.d) the requirement of certificates of bioethical qualification to publish the results of a research; 2.e) the incorporation of the REC tasks into the processes called "quality systems".